2018
DOI: 10.1016/j.mce.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic targets for growth arrest of colorectal cancer cells exposed to PTHrP

Abstract: Although PTHrP is implicated in several cancers, its role in chemoresistance is not fully elucidated. We found that in CRC cells, PTHrP exerts proliferative and protective effects and induces cell migration. The aim of this work was to further study the effects of PTHrP in CRC cells. Herein we evidenced, for the first time, that PTHrP induces resistance to CPT-11 in Caco-2 and HCT116 cells; although both cell lines responded to the drug through different molecular mechanisms, the chemoresistance by PTHrP in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 74 publications
4
26
0
Order By: Relevance
“…We evaluated if the response of HMEC-1 cells observed previously by us is the same or is different when these cells were exposed to TCMs which were pre-incubated for h at °C with the anti-VEGF antibody or with an appropriate isotype-matched control rabbit IgG. As shown in Figures 6A, B In previous studies, we obtained evidence that the hormone increases the proliferation, migration, survival and chemoresistance via MAPKs and PI3K/AKT signaling pathways in the colon cancer Caco-2 cells and HCT116 cells (Lezcano et al, 2013;Martín et al, 2014;Calvo et al, 2014;Calvo et al, 2017;Martín et al, 2018). ERK1/2 and AKT are central proteins in many cellular pathways leading to angiogenesis (Xu et al, 2015;Dong et al, 2017).…”
Section: Pthrp Promotes Tumor Angiogenesis Mainly Through Vegfsupporting
confidence: 61%
See 3 more Smart Citations
“…We evaluated if the response of HMEC-1 cells observed previously by us is the same or is different when these cells were exposed to TCMs which were pre-incubated for h at °C with the anti-VEGF antibody or with an appropriate isotype-matched control rabbit IgG. As shown in Figures 6A, B In previous studies, we obtained evidence that the hormone increases the proliferation, migration, survival and chemoresistance via MAPKs and PI3K/AKT signaling pathways in the colon cancer Caco-2 cells and HCT116 cells (Lezcano et al, 2013;Martín et al, 2014;Calvo et al, 2014;Calvo et al, 2017;Martín et al, 2018). ERK1/2 and AKT are central proteins in many cellular pathways leading to angiogenesis (Xu et al, 2015;Dong et al, 2017).…”
Section: Pthrp Promotes Tumor Angiogenesis Mainly Through Vegfsupporting
confidence: 61%
“…CRC is one of the main causes of death for cancer in the world (Siegelet al, 2017). chemoresistance and has a protective effect in conditions of apoptosis by the regulation of these signaling pathways (Lezcano et al, 2013;Martín et al, 2014;Calvo et al, 2014;Calvo et al, 2017;Martín et al, 2018). We think that other…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…By the implementation of multiple assays, we found that PTHrP (1-34) stimulates the cell cycle progression and proliferation of Caco-2 cells[ 37 , 38 ]. In line with these results, we reported similar effects induced by the cytokine in HCT116 cells, a CRC-derived cell line more undifferentiated and aggressive concerning Caco-2 cells, which also expresses PTHR1[ 39 ]. Despite the notable differences between Caco-2 cell and HCT116 cell phenotypes, the molecular mechanisms leading to these responses to the peptide in both CRC cells were similar and implied the activation of well-known deregulated pathways in CRC.…”
Section: Pthrp Promotes Cell Cycle Progression Proliferation and Migration Of Crc Cellssupporting
confidence: 62%